An Investigation into the Effect of Maltitol, Sorbitol, and Xylitol on the Formation of Carbamazepine Solid Dispersions Through Thermal Processing - Madan Sai Poka; Marnus Milne; Anita Wessels; Marique Aucamp (Pharmaceutics)
Background: Carbamazepine (CBZ) is a Biopharmaceutical Classification System (BCS) class II drug, that is practically insoluble in water, influencing the oral bioavailability. Polyols are highly hydrophilic crystalline carriers studied for their success in developing solid dispersions (SDs) for improved solubility and dissolution rate. Polyols are generally regarded as safe (GRAS) and maltitol (MAL), xylitol (XYL) and sorbitol (SOR) are among the approved polyols for market use. While xylitol (XYL) and sorbitol, have shown promise in improving the solubility and dissolution rates of poorly soluble drugs, their full potential in the context of improving the solubility of carbamazepine have not been thoroughly investigated. To the best of our knowledge, maltitol (MAL) was not studied previously as a carrier for preparing SDs. Hence, the purpose of this study was to investigate their use in the preparation of CBZ SDs by the fusion method. Methods: CBZ-polyol SDs were prepared in varying molar ratios (2:1, 1:1 and 1:2) and characterised for solid-state nature, solubility and in-vitro dissolution rate. Results: Solid-state characterisation of the CBZ-polyol SDs revealed the existence of the SDs as continuous glass suspensions with fine CBZ crystallites suspended in the amorphous polyol carriers. Among the polyols studied, XYL exhibited good miscibility with CBZ and showed significant improvement in the solubility and dissolution rate. The prepared SDs showed a 2 to 6-folds increase in CBZ solubility and 1.4 to 1.9-folds increase in dissolution rate in comparison with pure CBZ. Conclusions: The study explains the possible use of polyols (XYL and SOR) based SDs of BCS Class II drugs with good glass forming ability for enhanced solubility and dissolution.